2015
DOI: 10.3390/molecules201219742
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Electrical Properties of TTF-MPcs (M = Cu, Zn) Interfaces for Optoelectronic Applications

Abstract: Sandwich structures were fabricated by a vacuum deposition method using MPc (M = Cu, Zn), with a Tetrathiafulvalene (TTF) derivative, and Indium Tin Oxide (ITO) and aluminum electrodes. The structure and morphology of the deposited films were studied by IR spectroscopy, scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). The absorption spectra of TTF derivative-MPc (M = Cu, Zn) thin films deposited at room temperature were recorded in the spectral range 200-1000 nm. The optical band ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 37 publications
(81 reference statements)
3
2
0
Order By: Relevance
“…The diode-like behavior of this material could be attributed to the addition of TTF in the doping process, which leads to the formation of a homogeneous material with an apparent p-n junction. CuPc-TTF behavior could be attributed to the formation of alternative paths for carrier conduction due to p-type doping of the organic semiconductor with TTF, as has been reported in earlier studies [48]. It is worth mentioning that the measurements were done at room temperature under different illumination conditions in order to evaluate how would the device behave under the effect of solar irradiation, including natural and artificial white light, as well as red, orange, yellow, green, blue, and UV light.…”
Section: Resultssupporting
confidence: 60%
“…The diode-like behavior of this material could be attributed to the addition of TTF in the doping process, which leads to the formation of a homogeneous material with an apparent p-n junction. CuPc-TTF behavior could be attributed to the formation of alternative paths for carrier conduction due to p-type doping of the organic semiconductor with TTF, as has been reported in earlier studies [48]. It is worth mentioning that the measurements were done at room temperature under different illumination conditions in order to evaluate how would the device behave under the effect of solar irradiation, including natural and artificial white light, as well as red, orange, yellow, green, blue, and UV light.…”
Section: Resultssupporting
confidence: 60%
“…Results shown in Table 2 were compared to those reported in the literature, regarding typical values for doped MPcs such as M = Ni, Cu, Co, Pb, Zn and falling in the ranges of SCLC behavior such as P 0 between 8 × 10 43 to 1.15 × 10 47 J −1 •m −3 and 6 × 10 20 to 9. [28]. SCLC behavior is corroborated by comparison of the results to those found in the literature.…”
Section: Device Characterizationsupporting
confidence: 72%
“…This process leads to the formation of a homogeneous material with a behavior resembling that of a p-n junction. DSMB's larger conductivity could be attributed to the formation of alternative paths for carrier conduction when doping a p-type organic semiconductor with TTF, as has been reported in previous studies [28]. On the other hand, DSMD's behavior could also be related to the fact that, as has been demonstrated in other studies, TCNQ doping of p-type semiconductors, such as Na 2 Pc, could turn them into n-type semiconductors [29] [30].…”
Section: Device Characterizationsupporting
confidence: 64%
“…3a-a ’). Previous studies also reported the broad peak at 2θ value less than 30° for the amorphous nature of chitosan 68 . The peak at 25.3° was absent in the diffraction spectra of pure CS while it can be observed in the patterns of nanocomposites of CS-TiO 2 (diff.…”
Section: Resultsmentioning
confidence: 76%